Impact of social media on the sales of a Peruvian hotel corporations - Zimmermann-Blanco, Nicole; Nakazaki-Cipriano, Bruno; Esparza-Huamanchumo, Rosse Marie (Revista de Ciencias Sociales, 2024)
The research aimed to analyze the impact of social media management on the sales of a Peruvian hotel corporations. The study included interviews with top management, including managers from the sales department and marketing team, using a qualitative and basic approach with a phenomenological design. The interviews were analyzed based on two categories: marketing strategies in social media, as defined by Kiráľová & Pavlíček (2015), and the outcomes of using social media, according to Heller & Parasnis (2011); and Soteres (2011). The interviewees perceived a positive impact of the use of social media on the sales of the hotel chain. This effect can be primarily attributed to its role in achieving brand awareness nationally and globally. Similarly, social media disseminates information related to the hotel chain, providing the target audience a clearer understanding of the company’s offerings, including accommodation options and pricing details. Furthermore, social media facilitates seamless and direct communication with the target audience. In conclusion, this study contributes valuable insights that could easily be applied by hotel chains.